Political contestation and discourses of meaning: Revising Minnesota’s school integration revenue statute - Mattheis, Allison (Education Policy Analysis Archives, 2016)
The integration of students from diverse racial and ethnic backgrounds in public schools has been an issue of educational policy concern for several decades. Most school desegregation programs implemented in the United States post-Brown that relied on student busing and race-based school assignment were discontinued by the 1990s. In Minnesota, these were replaced with an approach that encouraged voluntary school integration efforts, supported with funding provided through State Statute 124D.86 to districts with racially identifiable schools or whose schools were racially isolated relative to neighboring communities. A legislatively mandated Integration Revenue Replacement Advisory Task Force was convened from November 2011 to February 2012 to frame the role of the state’s schools in addressing racial inequities and to recommend changes to existing policy. This article applies Fairclough and Fairclough’s (2012) analytic framework of political discourse as argumentation to examine the revision of this statute as a site of ideological contestation. The appointed members of this task force included professional educators, former legislators, faith leaders, and lawyers, and presented distinct epistemological beliefs regarding the purposes and roles of schools and of policy. Two competing claims for action were identified, summarized as “Bipartisan Compromise” and “Conservative Dissent.” This analysis reveals the effect of underlying values on developing particular claims for action made by Task Force members, and connects these values to divergent understandings of the purpose of state educational funding and the outcomes that public schooling should achieve.